3D modelling of substrate integrated waveguide (SIW) sensor for characterization of dielectric material - Nurazyyati, Inas (2022)
Dielectrics materials are a type of thin-film electronic material that is used in microelectronics. Active devices, such as transistors and their electrical isolation, such as capacitors, are used in a wide range of applications. High permittivity dielectric materials are utilized to improve the performance of semiconductor devices. Material development has begun with the discovery of thermoplastic resins, polyamides etc. These lead to the advancement of material characterization techniques such as using a variety of ways including planar resonators and substrate integrated waveguide (SIW).Various methods have been used for material characterization. However, these methods have issues that are specific to their uses. For instance, techniques that require vacuum cannot be used for analysing liquid or volatile chemicals. This limitation means that a given technique may have a limited range of applications. In this thesis, a new model design Substrate Integrated Waveguide (SIW) sensor for characterization of dielectric is presented. In order to enhance the accuracy of this sensor in extracting dielectric characteristics of materials, the performance parameter of this sensor is analysed and evaluated to assure performance using CST software. Concerning the modelling of the sensor, the steps started with validation of modelling technique from previous reported design research. After the technique of modelling is verified, the analysis for geometrical and dimensional changes such as the centre-to-centre distance ‘a’, the diameter of vias ‘d’ and the period between the vias ‘p’, are observed to meet the requirement design of this sensor. These analysis results are led to the modelling of own design, where resonant at 5.02GHz which covered in G-band range. The scattering parameters of this sensor are below -10dB in G-band which representing the good performance characteristics of this sensor. The simulation and measured scattering parameter have a good performance at 5.02GHz and 5.6GHz respectively which both frequencies covered in G-band range. Also, radiation patterns are analysed in order to validate the performance of the sensor. For the conclusion, the SIW sensor is designed on G-band operating at the frequency of 5.02GHz and a good radiation pattern with sidelobes of -2.7dB.